2020
DOI: 10.1187/cbe.20-03-0049
|View full text |Cite
|
Sign up to set email alerts
|

Is Active Learning Accessible? Exploring the Process of Providing Accommodations to Students with Disabilities

Abstract: This essay documents the challenges that active-learning practices pose for students with disabilities and how these challenges are currently being addressed by disability resource centers, or DRCs. Recommendations are presented for instructors and DRC staff who aim to create more inclusive active-learning science classes for students with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…There are likely many reasons why some students access institutional resources more than others; one reason may be that some students do not know that certain resources exist. For example, students with disabilities are sometimes unaware that Disability Resource Centers (DRCs) exist on their campus or do not know the range of services that DRCs provide (33)(34)(35). By listing general university resources on a syllabus, all students can become aware of opportunities that exist.…”
Section: Syllabi As Tools To Equitably Distribute Information Among Smentioning
confidence: 99%
“…There are likely many reasons why some students access institutional resources more than others; one reason may be that some students do not know that certain resources exist. For example, students with disabilities are sometimes unaware that Disability Resource Centers (DRCs) exist on their campus or do not know the range of services that DRCs provide (33)(34)(35). By listing general university resources on a syllabus, all students can become aware of opportunities that exist.…”
Section: Syllabi As Tools To Equitably Distribute Information Among Smentioning
confidence: 99%
“…To help facilitate compliance with these pieces of legislation, many colleges and universities have created disability resource centers (DRCs), 3 which are offices that provide academic and social services for students with disabilities, diagnosed medical conditions, and diagnosed mental health issues. 4 These services include a variety of ways to support students, such as in-person testing services, support in communicating with instructors for alternative assignments, assistance with classroom infrastructure and modifications, and assistive technologies (Section 504 of the Rehabilitation Act, 1973; Americans with Disabilities Act of 1990, 1990Gin et al, 2020). For traditional in-person courses, DRCs are typically helpful in providing accommodations to students in the form of interpreters, note-takers, transcriptionists, and test-taking services; however, studies have shown that undergraduates may be unaware that the office of the DRC exists, uncertain of the range of services that a DRC offers, or have difficulties advocating for accommodations, as college is often the first time students with disabilities are responsible for doing this on their own (Brinckerhoff, 1994;Dowrick et al, 2005;Eckes and Ochoa, 2005;Marshak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is part of an emergent body of research regarding the experiences of students with disabilities in undergraduate STEM contexts (Braun et al, 2017;Majocha et al, 2018;Gin et al, 2020;McCall et al, 2020;Pfeifer et al, 2020). Across these studies, a pattern appears.…”
Section: Resultsmentioning
confidence: 94%